Drug Standardization through Pharmacognostic Approaches and Estimation of Anticancer Potential of Chamomile ( Matricaria chamomilla L. ) using Prostate-Cancer cell lines: An In-vitro Study - Khan, Nida; Kalam, Mohd Afsahul; Alam, Mohd Tauseef; Haq, Syed Anam Ul; Showket, Wasia; Dar, Zahoor A.; Rafiq, Nida; Mushtaq, Waseem; Rafeeqi, Towseef Amin; Dar, Mohammad Yunis; Akbar, Seema; Butt, Tariq Ahmad; et al. (Journal of Cancer, 2023)
Cancer is the major challenge across world and the adenocarcinoma of prostate malignancy is the second most prevalent male cancer. Various medicinal plants are used for the treatment and management of various cancers. L., is one of the extensively used Unani medicament for the treatment of various type of diseases. In the current study we evaluated most of the parameters prescribed for drug standardization using pharmacognostic approaches. The 2,2 Diphenyl-1-picryl hydrazyl (DPPH) method was utilized for the analysis of antioxidant activity in the flower extracts of . Moreover, we analyzed the antioxidant and cytotoxic activity of ) through in-vitro method. DPPH (2,2-diphenyl-1-picryl-hydrazl-hydrate) method was utilized for the analysis of antioxidant activity in the flower extracts of . CFU and wound healing assay were performed to determine the anti-cancer activity. The results demonstrated that various extracts of fulfilled most of the parameters of drug standardization and contained good antioxidant and anticancer activities. The ethyl acetate showed higher anticancer activity followed by aqueous, hydroalcoholic, petroleum benzene and methanol by CFU method. Also, the wound healing assay demonstrated that ethyl acetate extract has more significant effect followed by methanol and petroleum benzene extract on prostate cancer cell line (C4-2). The current study concluded that the extract of flowers could act as good source of natural anti-cancer compounds.